Sodium-ion battery with long cycle life and preparation method thereof

By adding dopants and carbon sources to the positive and negative electrode materials of sodium ion batteries, an open pore is formed, and a high-concentration sodium salt electrolyte is used to solve the problem of volume expansion and irreversible capacity loss of sodium ion batteries during charging and discharging, and a long cycle life and high stability battery performance is achieved. It is suitable for deep-sea special batteries.

CN120261678APending Publication Date: 2025-07-04HAINAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510430456.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-08
Publication Date
2025-07-04

AI Technical Summary

Technical Problem

The existing sodium ion batteries cannot effectively suppress lattice distortion during the charge and discharge cycle, resulting in battery volume expansion, low structural stability, and the sodium ion expansion path in the battery has not been reduced, resulting in a high irreversible capacity loss for the first cycle of the battery, limiting its application in deep-sea special batteries.

Method used

By adding dopants and carbon sources to the positive electrode material, lattice distortion is suppressed and conductivity is improved; open pores are formed in the negative electrode material to increase the diffusion rate of sodium ions; electrolytes with high concentrations of sodium salts and specific solvents are used to promote the formation of stable SEI films; and volume expansion is alleviated through the nanocomposite structure.

Benefits of technology

It significantly improves the cycle life and comprehensive performance of sodium ion batteries, and is suitable for deep-sea special batteries, reducing costs and enhancing the stability and safety of the batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120261678A_ABST
    Figure CN120261678A_ABST
Patent Text Reader

Abstract

The invention discloses a long-cycle-life sodium-ion battery and a preparation method thereof, and relates to the technical field of sodium-ion batteries, the sodium-ion battery comprises a positive electrode material, a negative electrode material, a diaphragm and an electrolyte, and the preparation method comprises the steps of preparing the positive electrode material, preparing the negative electrode material, preparing an electrode solution and packaging the sodium-ion battery; the doping agent is added in the preparation of the positive electrode material to inhibit lattice distortion and reduce volume expansion in the battery cycle process, the carbon source is added to realize carbon coating, reduce interface side reaction and improve conductivity, and an open pore channel is formed through pre-oxidation of hard carbon in the preparation of the negative electrode material, so that the conductivity of the battery is improved. According to the present invention, the high-concentration sodium salt is adopted as the electrolyte so as to improve the sodium ion diffusion rate, reduce the surface active site and inhibit the electrolyte decomposition, and the high-concentration sodium salt is adopted as the electrolyte so as to promote the formation of the stable SEI film, such that the long cycle life of the sodium ion battery is improved, and the sodium ion battery can be well applied to the deep sea special battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium-ion batteries, and particularly to a sodium-ion battery with a long cycle life and a preparation method thereof. Background Art

[0002] Deep-sea special batteries are battery systems designed specifically for operation under extreme water pressure and harsh marine environments. They can provide stable power support in deep-sea operations and are widely used in high-tech fields such as deep-sea exploration, power supply for subsea equipment, unmanned submersibles, underwater robots (AUVs, ROVs), ocean buoy systems, and ocean research instruments. Since sodium resources are abundant and inexpensive, the application of sodium-ion batteries in deep-sea special batteries can significantly reduce the overall cost. In addition, the high safety of sodium-ion batteries gives them significant advantages in deep-sea special batteries. Moreover, the wide temperature characteristics of sodium-ion batteries enable them to adapt to temperature changes in the deep-sea environment, ensuring the stable operation of the batteries in the deep sea.

[0003] Sodium-ion batteries are secondary batteries, i.e., rechargeable batteries, which mainly rely on the movement of sodium ions between the positive and negative electrodes to work. Similar to the working principle of lithium-ion batteries, during the charge and discharge process of sodium-ion batteries, Na+ intercalates and deintercalates between the two electrodes. During charging, Na+ deintercalates from the positive electrode and intercalates into the negative electrode through the electrolyte, and vice versa during discharging. The electrode materials used in sodium-ion batteries are mainly high-concentration sodium salts, which are more abundant in reserves and cheaper than lithium salts. Since sodium ions are larger than lithium ions, when the requirements for weight and energy density are not high, sodium-ion batteries are a cost-effective alternative.

[0004] With the transformation of the global energy structure and the rapid development of new energy vehicles, the demand for high-energy-density, long-cycle-life, and low-cost energy storage technologies is increasing day by day. As a potential alternative to lithium-ion batteries for energy storage, sodium-ion batteries have advantages such as rich resources, environmental friendliness, and low cost. The research and development of sodium-ion battery technology are receiving extensive attention from governments and enterprises around the world.

[0005] Most of the existing sodium-ion batteries have a single composition and cannot effectively inhibit lattice distortion during the charge and discharge cycle process, resulting in easy volume expansion of the battery, low structural stability, and insufficient conductivity of the positive electrode material in the battery. In addition, the sodium ion diffusion path in the battery has not been reduced, resulting in a high irreversible capacity loss in the first cycle of the battery, thus leading to a low cycle life of the sodium-ion battery, and further making it difficult for the large-scale energy storage application of sodium-ion batteries and unable to be well applied in deep-sea special batteries. Therefore, the present invention proposes a sodium-ion battery with a long cycle life and a preparation method thereof to solve the problems existing in the prior art. Summary of the Invention

[0006] In view of the above problems, the object of the present invention is to provide a sodium-ion battery with a long cycle life and a preparation method thereof, which solves the problems that in the existing sodium-ion battery during the charge and discharge cycle process, lattice distortion cannot be effectively inhibited, resulting in easy volume expansion of the battery, low structural stability, insufficient conductivity of the positive electrode material in the battery, and the sodium ion diffusion path in the battery not being reduced, resulting in a high irreversible capacity loss in the first cycle of the battery.

[0007] To achieve the object of the present invention, the present invention is realized through the following technical solutions: A sodium-ion battery with a long cycle life includes a positive electrode material, a negative electrode material, a separator, and an electrolyte. The positive electrode material and the negative electrode material are separated by the separator, the electrolyte is filled between the positive electrode material and the negative electrode material, a positive electrode current collector is covered on the positive electrode material, and a negative electrode current collector is covered on the negative electrode material. The positive electrode material is made of a first metal salt, a dopant, and a carbon source in a mass ratio of 100:3-5:10-30. The negative electrode material is made of a composite biomass and a second metal salt in a mass ratio of 20:1-2. The separator is made of a ceramic-coated separator and coated with an alumina coating. The electrolyte is made of a high-concentration sodium salt, a solvent, a film-forming additive, and a flame retardant additive in a mass ratio of 2-4:20:1:2.

[0008] Further improvement lies in that: the first metal salt is selected from one of manganese salts or nickel salts, the dopant is selected from one of magnesium oxide or titanium dioxide, and the carbon source is selected from one of glucose or sucrose.

[0009] Further improvement lies in that: the composite biomass is prepared by mixing starch and phenolic resin in a mass ratio of 2-3:1, and the second metal salt is selected from one of tin salts or copper salts.

[0010] Further improvement lies in that: the high-concentration sodium salt is selected from one of sodium hexafluorophosphate or sodium bis(fluorosulfonyl)imide, the ether solvent is selected from one of ethylene glycol dimethyl ether or tetrahydrofuran, the film-forming additive is selected from one of fluoroethylene carbonate or vinylene carbonate, and the flame retardant additive is selected from one of triphenyl phosphate or trimethyl phosphate.

[0011] A preparation method of a sodium-ion battery with a long cycle life includes the following steps:

[0012] Step 1: First, weigh the first metal salt, the dopant, and the carbon source according to the mass ratio of 100:3-5:10-30 respectively. Then mix the weighed first metal salt and the dopant and perform a calcination treatment. After sintering, the obtained positive electrode material is refined by ball milling. The carbon source is added to the positive electrode particles obtained by ball milling and mixed continuously, and heat treatment is carried out in an inert atmosphere. After the heat treatment is completed, the positive electrode material is obtained.

[0013] Step 2: Weigh the composite biomass and the second metal salt according to a mass ratio of 20:1 to 2:1 respectively. Then heat the composite biomass in an air atmosphere, and then heat and carbonize the composite biomass at a high temperature in an inert atmosphere to generate hard carbon and mix it with the second metal salt. After mixing evenly, use high-energy ball milling to crush the mixture into nano-sized particles, and then perform high-temperature treatment in an inert atmosphere to obtain the negative electrode material;

[0014] Step 3: Weigh the high-concentration sodium salt, ether solvent, film-forming additive, and flame retardant additive according to a mass ratio of 2 - 4:20:1:2 respectively. Then mix the weighed high-concentration sodium salt and ether solvent evenly, and then add the film-forming additive and flame retardant additive at one time and continue to mix evenly to obtain the electrolyte;

[0015] Step 4: Use a flexible binder to bond and cover the positive electrode current collector and the negative electrode current collector on the positive electrode material and the negative electrode material respectively, and then encapsulate the positive electrode material, the negative electrode material, the separator, and the electrolyte into a sodium-ion battery to obtain a finished sodium-ion battery with a long cycle life.

[0016] Further improvement lies in: in the above Step 1, after the first metal salt and the dopant are mixed, they are pre-calcined at a temperature of 600 - 800 °C first, and then sintered at a temperature of 900 - 1000 °C. The inert atmosphere is selected from one of argon or nitrogen.

[0017] Further improvement lies in: in the above Step 2, the composite biomass and the second metal salt are first heated in an air atmosphere at 200 - 400 °C, and then carbonized at a high temperature in an inert atmosphere at 800 - 1200 °C. The inert atmosphere is selected from one of argon or nitrogen.

[0018] Further improvement lies in: in the above Step 4, the flexible binder is selected from one of sodium carboxymethyl cellulose binder or styrene-butadiene rubber binder. The positive electrode current collector is aluminum foil, and the negative electrode current collector is copper foil.

[0019] Further improvement lies in: in the above Step 4, sodium ions are pre-supplemented to the negative electrode material before encapsulation. The specific steps are: using a Red-Al solution as a pre-sodiation reagent, immersing the negative electrode material in it, and heating at a temperature of 180 - 200 °C to pre-embed sodium ions into the negative electrode material.

[0020] The beneficial effects of the present invention are as follows: A dopant is added in the preparation of the cathode material to inhibit lattice distortion, reduce volume expansion during battery cycling, and achieve carbon coating by adding a carbon source, which can reduce interfacial side reactions and improve conductivity. In the preparation of the anode material, open pores are formed through the pre-oxidation of hard carbon to enhance the sodium ion diffusion rate, reduce surface active sites, and inhibit electrolyte decomposition. In addition, by using a high-concentration sodium salt as the electrolyte, the formation of a stable SEI film can be promoted, and an ether solvent is used to replace the traditional carbonate solvent, which can improve low-temperature performance and interfacial compatibility, thereby improving the comprehensive performance and long cycle life of the sodium-ion battery, and it can be well applied to deep-sea special batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a schematic process diagram of the preparation method of the long cycle life sodium-ion battery of the present invention. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0022] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative work belong to the scope of protection of the present invention.

[0023] A sodium-ion battery (Sodium-Ion Battery, SIB) is an electrochemical energy storage device based on the migration of sodium ions (Na + ) between the positive and negative electrodes. Its working principle is similar to that of a lithium-ion battery (LIB), but sodium resources are used to replace lithium resources. Due to its low cost, rich resources, and potential high safety, the sodium-ion battery is regarded as an important supplement to the lithium-ion battery, especially in the fields of energy storage and low-speed electric vehicles, etc., and has broad application prospects.

[0024] Embodiment 1

[0025] This embodiment provides a long cycle life sodium-ion battery, which includes a cathode material as the battery cathode, an anode material for the battery anode, a separator for separating the cathode material and the anode material, and an electrolyte filled inside the sodium-ion battery. The electrolyte is filled between the cathode material and the anode material. A positive electrode current collector made of an aluminum foil material is covered on the cathode material, and a negative electrode current collector made of a copper foil material is covered on the anode material;

[0026] The cathode material of this embodiment is made from a first metal salt, a dopant, and a carbon source in a mass ratio of 100:3:10. The first metal salt is MnCO3, the dopant is magnesium oxide, and the carbon source is glucose. The dopant is added to the first metal salt to inhibit lattice distortion and reduce volume expansion during battery cycling. Carbon coating is achieved by adding the carbon source, which can reduce interfacial side reactions and improve conductivity;

[0027] The anode material of this embodiment is made from a composite biomass and a second metal salt in a mass ratio of 20:1. The composite biomass is prepared by mixing starch and phenolic resin in a mass ratio of 2:1, and the second metal salt is SnCl2;

[0028] The separator of this embodiment is made by using a ceramic-coated separator and coating an alumina coating to improve thermal stability and prevent dendrite penetration,

[0029] The electrolyte of this embodiment is made from a high-concentration sodium salt, a solvent, a film-forming additive, and a flame retardant additive in a mass ratio of 2:20:1:2. The high-concentration sodium salt is sodium hexafluorophosphate, the ether solvent is ethylene glycol dimethyl ether, the film-forming additive is fluoroethylene carbonate, and the flame retardant additive is triphenyl phosphate.

[0030] See Figure 1 , this embodiment also provides a preparation method for a sodium-ion battery with a long cycle life, including the following steps:

[0031] Step 1: Weigh the first metal salt, the dopant, and the carbon source and prepare the cathode material

[0032] First, weigh the first metal salt, the dopant, and the carbon source according to the mass ratio of 100:3:10 respectively. Then mix the weighed first metal salt and the dopant and pre-calcine them at a temperature of 600 °C to decompose the salts to form an oxide precursor. Next, sinter them at a temperature of 900 °C to uniformly dope the dopant into the lattice. After sintering, the obtained cathode material is refined by ball milling to improve uniformity. The carbon source is added to the cathode particles obtained by ball milling and mixed continuously to form a uniform slurry, and heat treatment is carried out in an argon or nitrogen atmosphere. The carbon source decomposes into an amorphous carbon layer to coat the surface of the cathode particles, forming a conductive network, enhancing electron conduction, isolating the electrolyte, and reducing the dissolution of transition metals. After the heat treatment is completed, the cathode material is obtained;

[0033] Step 2: Weigh the composite biomass and the second metal salt and prepare the anode material

[0034] Weigh the composite biomass and the second metal salt respectively according to a mass ratio of 20:1. Then heat the composite biomass in an air atmosphere at 200 °C to form a partially oxidized structure. Next, heat the composite biomass at a high temperature for carbonization in an argon or nitrogen atmosphere at 800 °C to generate hard carbon containing micropores / mesopores. Pre-oxidation forms open pores to enhance the sodium ion diffusion rate, reduce surface active sites, and inhibit the decomposition of the electrolyte.

[0035] The hard carbon is then mixed with the second metal salt. After mixing evenly, the mixture is pulverized into nanoparticles by high-energy ball milling. The use of a nano-composite structure can alleviate the volume expansion problem of the battery. Then, it is heat-treated at a high temperature in an inert atmosphere to obtain the negative electrode material.

[0036] Step 3: Weigh a high-concentration sodium salt, an ether solvent, a film-forming additive, and a flame retardant additive and prepare an electrolyte solution.

[0037] Weigh the high-concentration sodium salt, the ether solvent, the film-forming additive, and the flame retardant additive respectively according to a mass ratio of 2:20:1:2. Then mix the weighed high-concentration sodium salt and the ether solvent evenly. Next, add the film-forming additive and the flame retardant additive at one time and continue to mix evenly to obtain the electrolyte solution. By using a high-concentration sodium salt as the electrolyte solution, it can promote the formation of a stable SEI film. By using an ether solvent to replace the traditional carbonate solvent, it can improve the low-temperature performance and interface compatibility. And by introducing the film-forming additive and the flame retardant additive, side reactions can be reduced.

[0038] Step 4: Package the positive electrode material, the negative electrode material, the separator, and the electrolyte solution into a sodium-ion battery.

[0039] Pre-supplement sodium ions to the negative electrode material to compensate for the sodium loss in the first cycle and improve the reversible capacity and the first Coulomb efficiency of the battery. The specific steps are as follows: Use a Red-Al solution as the pre-sodiation reagent, immerse the negative electrode material in it, and heat it at a temperature of 180 °C to pre-embed sodium ions into the negative electrode material.

[0040] Then, use sodium carboxymethylcellulose adhesive or styrene-butadiene rubber adhesive to bond and cover the positive electrode current collector and the negative electrode current collector on the positive electrode material and the negative electrode material respectively. The use of a flexible adhesive can maintain the electrode integrity to a certain extent. Then, package the positive electrode material, the negative electrode material, the separator, and the electrolyte solution into a sodium-ion battery to obtain a finished sodium-ion battery with a long cycle life.

[0041] Example 2

[0042] This embodiment provides a sodium-ion battery with a long cycle life, including a positive electrode material serving as the battery's positive electrode, a negative electrode material for the battery's negative electrode, a separator for separating the positive electrode material and the negative electrode material, and an electrolyte filled inside the sodium-ion battery. The electrolyte is filled between the positive electrode material and the negative electrode material. A positive electrode current collector made of aluminum foil material is covered on the positive electrode material, and a negative electrode current collector made of copper foil material is covered on the negative electrode material;

[0043] The positive electrode material of this embodiment is made from a first metal salt, a dopant, and a carbon source in a mass ratio of 20:1:6. The first metal salt is NiSO4, the dopant is titanium dioxide, and the carbon source is sucrose. The dopant is added to the first metal salt to inhibit lattice distortion and reduce volume expansion during battery cycling. By adding the carbon source to achieve carbon coating, interfacial side reactions can be reduced and conductivity can be improved;

[0044] The negative electrode material of this embodiment is made from a composite biomass and a second metal salt in a mass ratio of 10:1. The composite biomass is prepared by mixing starch and phenolic resin in a mass ratio of 3:1, and the second metal salt is CuSO4;

[0045] The separator of this embodiment is made of a ceramic-coated separator and coated with an alumina coating to enhance thermal stability and prevent dendrite penetration,

[0046] The electrolyte of this embodiment is made from a high-concentration sodium salt, a solvent, a film-forming additive, and a flame retardant additive in a mass ratio of 4:20:1:2. The high-concentration sodium salt is sodium bis(fluorosulfonyl)imide, the ether solvent is tetrahydrofuran, the film-forming additive is vinylene carbonate, and the flame retardant additive is trimethyl phosphate.

[0047] See Figure 1 , this embodiment also provides a preparation method for a sodium-ion battery with a long cycle life, including the following steps:

[0048] Step 1: Weigh the first metal salt, the dopant, and the carbon source and prepare the positive electrode material

[0049] First, weigh the first metal salt, the dopant, and the carbon source according to the mass ratio of 20:1:6 respectively. Then mix the weighed first metal salt and the dopant and pre-calcine them at a temperature of 800 °C to decompose the salts to form an oxide precursor. Then sinter them at a temperature of 1000 °C to uniformly dope the dopant into the lattice. After sintering, the obtained positive electrode material is refined by ball milling to improve uniformity. The carbon source is added to the positive electrode particles obtained by ball milling and mixed continuously to form a uniform slurry, and heat treatment is carried out in an argon or nitrogen atmosphere. The carbon source decomposes into an amorphous carbon layer covering the surface of the positive electrode particles, forming a conductive network, enhancing electron conduction, isolating the electrolyte, and reducing the dissolution of transition metals. After the heat treatment is completed, the positive electrode material is obtained;

[0050] Step 2: Weigh the composite biomass and the second metal salt and prepare the negative electrode material

[0051] First, weigh the composite biomass and the second metal salt according to a mass ratio of 10:1 respectively. Then, heat the composite biomass in an air atmosphere at 400 °C to form a partially oxidized structure. Next, heat the composite biomass at a high temperature of 1200 °C in an argon or nitrogen atmosphere for carbonization to generate hard carbon containing micropores / mesopores. Pre-oxidation forms open pores to enhance the sodium ion diffusion rate, reduce surface active sites, and inhibit the decomposition of the electrolyte;

[0052] The hard carbon is then mixed with the second metal salt. After mixing evenly, the mixture is pulverized into nanoscale particles by high-energy ball milling. The use of a nanocomposite structure can alleviate the problem of volume expansion of the battery. Then, it is heat-treated at a high temperature in an inert atmosphere to obtain the negative electrode material;

[0053] Step 3: Weigh the high-concentration sodium salt, ether solvent, film-forming additive, and flame retardant additive and prepare the electrolyte

[0054] First, weigh the high-concentration sodium salt, ether solvent, film-forming additive, and flame retardant additive according to a mass ratio of 4:20:1:2 respectively. Then, mix the weighed high-concentration sodium salt and ether solvent evenly. Next, add the film-forming additive and flame retardant additive at one time and continue to mix evenly to obtain the electrolyte. By using a high-concentration sodium salt as the electrolyte, it can promote the formation of a stable SEI film. By using an ether solvent to replace the traditional carbonate solvent, it can improve the low-temperature performance and interfacial compatibility. And by introducing the film-forming additive and flame retardant additive, side reactions can be reduced;

[0055] Step 4: Package the positive electrode material, negative electrode material, separator, and electrolyte into a sodium-ion battery

[0056] Pre-supplement sodium ions to the negative electrode material to compensate for the sodium loss in the first cycle and improve the reversible capacity and first Coulomb efficiency of the battery. The specific steps are as follows: Use a Red-Al solution as the pre-sodiation reagent, immerse the negative electrode material in it, and heat it at a temperature of 200 °C to pre-embed sodium ions into the negative electrode material;

[0057] Then, use sodium carboxymethyl cellulose adhesive or styrene-butadiene rubber adhesive to bond and cover the positive electrode current collector and the negative electrode current collector on the positive electrode material and the negative electrode material respectively. The use of a flexible binder can maintain the electrode integrity to a certain extent. Then, package the positive electrode material, negative electrode material, separator, and electrolyte into a sodium-ion battery to obtain the finished product of a sodium-ion battery with a long cycle life.

[0058] The sodium-ion batteries prepared in Example 1 and Example 2 were subjected to charge-discharge cycles at room temperature, and a commercially available traditional sodium-ion battery (LiitoKala Si4500 32700 4500 mAh large-capacity 3V sodium-ion rechargeable core battery) was used as a comparison. The current density was 1 A / g. -1 , the voltage range was 0.5 - 3.5 V, and the cycle was 150 times. Record the initial capacity of the sodium-ion battery and the capacity after 150 cycles, and calculate the average capacity attenuation rate per cycle. The average capacity attenuation rate per cycle = (initial capacity - capacity after 150 cycles) / initial capacity / 150. The test results are shown in Table 1 below:

[0059] Table 1 Test Results Table

[0060] Average capacity attenuation rate per turn Specific capacity Example 1 0.15% 355 Example 2 0.14% 350 Comparative example 0.36% 325

[0061] As can be seen from Table 1 above, compared with the traditional sodium-ion battery, the sodium-ion batteries prepared in Example 1 and Example 2 of the present invention have a lower capacity attenuation rate, that is, a higher cycle life.

[0062] The above are only the preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A sodium-ion battery with a long cycle life, comprising a positive electrode material, a negative electrode material, a separator and an electrolyte, characterized in that: The positive electrode material and the negative electrode material are separated by a separator. The electrolyte is filled between the positive electrode material and the negative electrode material. The positive electrode material is covered with a positive electrode current collector, and the negative electrode material is covered with a negative electrode current collector. The positive electrode material is made of a first metal salt, a dopant, and a carbon source in a mass ratio of 100:3-5:10-30. The negative electrode material is made of a composite biomass and a second metal salt in a mass ratio of 20:1-2. The separator is made of a ceramic-coated separator and coated with an alumina coating. The electrolyte is made of a high-concentration sodium salt, a solvent, a film-forming additive, and a flame retardant additive in a mass ratio of 2-4:20:1:

2.

2. The long-cycle-life sodium-ion battery according to claim 1, wherein: The first metal salt is selected from one of manganese salts or nickel salts. The dopant is selected from one of magnesium oxide or titanium dioxide. The carbon source is selected from one of glucose or sucrose.

3. A sodium-ion battery with a long cycle life according to claim 1, characterized in that: The composite biomass is prepared by mixing starch and phenolic resin in a mass ratio of 2-3:

1. The second metal salt is selected from one of tin salts or copper salts.

4. A sodium-ion battery with a long cycle life according to claim 1, characterized in that: The high-concentration sodium salt is selected from one of sodium hexafluorophosphate or sodium bis(fluorosulfonyl)imide. The ether solvent is selected from one of ethylene glycol dimethyl ether or tetrahydrofuran. The film-forming additive is selected from one of fluoroethylene carbonate or vinylene carbonate. The flame retardant additive is selected from one of triphenyl phosphate or trimethyl phosphate.

5. A preparation method of a sodium ion battery with a long cycle life as described in claim 1, characterized in that, It includes the following steps: Step 1: First, weigh the first metal salt, the dopant, and the carbon source according to a mass ratio of 100:3-5:10-30 respectively. Then mix the weighed first metal salt and the dopant and perform a calcination treatment. After sintering, the obtained positive electrode material is refined by ball milling. The carbon source is added to the positive electrode particles obtained by ball milling and mixed continuously, and heat treatment is performed in an inert atmosphere. After the heat treatment is completed, the positive electrode material is obtained. Step 2: First, weigh the composite biomass and the second metal salt according to a mass ratio of 20:1-2 respectively. Then heat the composite biomass in an air atmosphere, and then heat and carbonize the composite biomass at a high temperature in an inert atmosphere to generate hard carbon and mix it with the second metal salt. After mixing evenly, the mixture is pulverized into nanoscale particles by high-energy ball milling, and then heat-treated at a high temperature in an inert atmosphere to obtain the negative electrode material. Step 3: First, weigh the high-concentration sodium salt, the ether solvent, the film-forming additive, and the flame retardant additive according to a mass ratio of 2-4:20:1:2 respectively. Then mix the weighed high-concentration sodium salt and the ether solvent evenly, and then add the film-forming additive and the flame retardant additive at one time and continue to mix evenly to obtain the electrolyte. Step 4: Use a flexible binder to bond and cover the positive electrode current collector and the negative electrode current collector on the positive electrode material and the negative electrode material respectively. Then encapsulate the positive electrode material, the negative electrode material, the separator, and the electrolyte into a sodium-ion battery to obtain a finished sodium-ion battery with a long cycle life.

6. The preparation method of a sodium-ion battery with a long cycle life according to claim 5, characterized in that: In the step 1, after the first metal salt and the dopant are mixed, they are first pre-calcined at a temperature of 600-800 °C, and then sintered at a temperature of 900-1000 °C. The inert atmosphere is selected from one of argon or nitrogen.

7. The preparation method of a sodium ion battery with a long cycle life according to claim 5, characterized in that: In the second step, the composite biomass and the second metal salt are first heated in an air atmosphere at 200-400°C, and then subjected to high-temperature carbonization in an inert atmosphere at 800-1200°C. The inert atmosphere is selected from one of argon or nitrogen.

8. The preparation method of a sodium-ion battery with a long cycle life according to claim 5, wherein: In the fourth step, the flexible binder is selected from one of sodium carboxymethyl cellulose binder or styrene-butadiene rubber binder. The positive current collector is aluminum foil, and the negative current collector is copper foil.

9. The preparation method of a sodium-ion battery with a long cycle life according to claim 5, characterized in that: In the fourth step, the negative electrode part material is pre-supplemented with sodium ions before encapsulation. The specific steps are as follows: Using a Red-Al solution as a pre-sodiation reagent, immersing the negative electrode part material therein, and heating at a temperature of 180-200°C to pre-embed sodium ions into the negative electrode material.